Nanosheet composite hollow sphere and preparation method and application thereof
By using nanosheet composite hollow spheres as capacitance desalination electrode materials, and using alkaline nickel carbonate and nickel hydroxide as nanosheet components, the problem of low adsorption amount of carbon materials in the existing capacitance desalination technology is solved, and efficient capacitance desalination performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202211148942.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-09-20
AI Technical Summary
Among the existing capacitance desalination technology, carbon materials, as electrode materials, have problems with low adsorption amount and low charge utilization, and there are few researches on the application of hydroxides and alkali carbonates in capacitance desalination materials.
Nanosheet composite hollow spheres were used as electrode materials for capacitance desalting, and nanosheet composite hollow spheres with large specific surface area were prepared by hydrothermal reaction method by using alkaline nickel carbonate and nickel hydroxide as components of nanosheets.
It has achieved the provision of more ion adsorption active sites in the capacitor desalination process, improved the desalination performance and cycle stability of the electrode materials, and has good practicality and industrial application prospects.
Smart Images

Figure CN115583696B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano materials, and in particular to a nano sheet composite hollow sphere and a preparation method and application thereof. Background Art
[0002] The shortage and pollution of water resources are important factors restricting the development of today's society. As a new water treatment technology, capacitive desalination technology is based on double-layer or pseudocapacitor electrosorption desalination, and realizes adsorption and desorption through the relative movement of charged particles under different directional potentials. Compared with traditional reverse osmosis technology, capacitive desalination technology has attracted extensive attention from researchers in the field of water treatment due to its advantages such as environmental friendliness, low energy consumption, high efficiency and no secondary pollution.
[0003] In the field of water treatment using capacitive desalination technology, the most studied electrode materials for capacitive desalination are carbon materials. Porous carbon, graphene, carbon nanotubes, carbon aerogels and their composite materials have been developed. Carbon materials have good stability but generally have problems such as low adsorption and low charge utilization. In recent years, polymers represented by polyaniline, transition metal sulfides represented by molybdenum disulfide, transition metal oxides represented by manganese dioxide, transition metal carbides represented by MXene, and polyanionic compounds represented by iron phosphate have been developed. However, there are few studies on the application of hydroxides and basic carbonates in capacitive desalination materials.
[0004] At present, the application research of basic nickel carbonate / nickel hydroxide related materials is mainly concentrated in the fields of hydrogen production by electrolysis of water, zinc ion batteries, supercapacitors, photothermal catalysis, CO2 electroreduction, TOC organic matter degradation, near-infrared nanosensor probes, alkaline batteries, electrochemical degradation of methyl orange, etc. There is no research on its application in capacitor desalination electrode materials. Basic carbonate, as a natural mineral, is mainly used to extract nickel. It is low in price and has a simple synthesis process. Therefore, it is of great significance to expand its application directions. Summary of the invention
[0005] The purpose of the present invention is to overcome the above problems and provide a nanosheet composite hollow sphere and a preparation method and application thereof. The nanosheet composite hollow sphere material described in the present invention has a novel morphology and a large specific surface area. When it is used as an electrode material for capacitive desalination, it has excellent capacitive desalination performance and can be reused. The preparation method is simple and has great industrial application prospects.
[0006] In order to achieve the above object, the present invention provides a nanosheet composite hollow sphere, wherein the particle size of the hollow sphere is 2-3 μm, and the thickness of the sphere wall of the hollow sphere is 300-500 nm;
[0007] The length of the nanosheet is 300-500 nm, and the thickness of the nanosheet is 5-10 nm;
[0008] The components of the nanosheets include basic nickel carbonate and nickel hydroxide.
[0009] The second aspect of the present invention provides a method for preparing nanosheet composite hollow spheres, the method comprising the following steps:
[0010] (1) mixing nickel nitrate hexahydrate, disodium ethylenediaminetetraacetate, water and an optional surfactant, and then performing a hydrothermal reaction;
[0011] (2) adding an aqueous ammonia solution to the solution after the reaction in step (1), and then performing a hydrothermal reaction again;
[0012] The weight ratio of nickel nitrate hexahydrate to disodium ethylenediaminetetraacetate is 1-2:1;
[0013] The volume ratio of ammonia solution to water is 2-4:35;
[0014] The weight ratio of disodium edetate to water is 0.9-1.35:35.
[0015] Preferably, the weight ratio of nickel nitrate hexahydrate to the surfactant is 1:0.3-1.
[0016] Preferably, the concentration of the aqueous ammonia solution is 25-28 wt%.
[0017] Preferably, in step (1), the conditions of the hydrothermal reaction include: reaction temperature of 150-200° C., and reaction time of 10-15 h.
[0018] Preferably, in step (2), the conditions of the hydrothermal reaction include: reaction temperature of 150-200° C., and reaction time of 10-15 h.
[0019] The third aspect of the present invention also provides a nanosheet composite hollow sphere prepared by the above method.
[0020] The fourth aspect of the present invention further provides an electrode material for capacitive desalination, wherein the electrode material for capacitive desalination comprises the above-mentioned nanosheet composite hollow sphere.
[0021] A fifth aspect of the present invention provides an application of the above-mentioned capacitor desalination electrode material in water treatment.
[0022] Beneficial effects of the present invention:
[0023] 1. The nanosheet composite hollow spheres of the present invention have novel morphology, large specific surface area, and suitable pore size distribution. As electrode materials for capacitive desalination, they can provide more active sites for ion adsorption during the capacitive desalination process. The pore size distribution inside the material and the unique hollow sphere structure are more conducive to the penetration of ions in the electrolyte solution, which can better enable the electrode material to fully contact with the electrolyte solution and improve the desalination performance of the electrode material.
[0024] 2. The nanosheet composite hollow spheres of the present invention are used as electrode materials for capacitive desalination. In the process of capacitive desalination, under an applied voltage of 1.2V, in a 500ppm NaCl salt solution, the salt adsorption capacity of the material can reach up to 41.3mg / g, and in the subsequent 20 cycles for up to 3 days, its adsorption performance can be stably maintained at 100%, showing a high ion adsorption capacity and very excellent cycle stability, and can adapt to frequent voltage changes. The material surface can quickly respond to the transition of electrical adsorption-desorption. The various properties of the nanosheet composite hollow spheres can meet the requirements of capacitive desalination electrode materials, and can be used very well as capacitive desalination electrode materials for water treatment, showing good practicality;
[0025] 3. The components of the nanosheet composite hollow spheres described in the present invention include basic nickel carbonate and nickel hydroxide. There are currently no reports on the use of basic carbonate materials as capacitor desalination electrode materials. The present invention is the first to propose the use of basic nickel carbonate and nickel hydroxide for compounding to prepare nanosheet composite hollow sphere materials with a large specific surface area for capacitor desalination electrode materials, which provides a new direction and new ideas for the field of capacitor desalination electrode materials and expands the boundaries of the field of capacitor desalination electrode materials.
[0026] 4. The method described in the present invention has a simple preparation process, no solvent pollution in the preparation process, is more green and environmentally friendly, and the preparation process is safe and non-toxic, and has great industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the XRD pattern of the nanosheet composite hollow sphere prepared in Example 1;
[0028] Figure 2 is the infrared spectrum of the nanosheet composite hollow sphere prepared in Example 1;
[0029] Figure 3 The nitrogen adsorption-desorption curve and pore size distribution diagram of the nanosheet composite hollow sphere prepared in Example 1;
[0030] Figure 4The SEM morphology images of the nanosheet composite hollow spheres prepared in Examples 1-3 and the products prepared in Comparative Examples 1-2, and the TEM morphology image of the nanosheet composite hollow spheres prepared in Example 1;
[0031] Figure 5 is a CV curve diagram of the nanosheet composite hollow spheres prepared in Example 1 as a capacitor desalination electrode material;
[0032] Figure 6 is a GCD curve diagram of the nanosheet composite hollow spheres prepared in Example 1 as a capacitive desalination electrode material;
[0033] Figure 7 This is a graph showing the conductivity change of the electrolyte in the state of adsorption-desorption of ions by the nanosheet composite hollow spheres prepared in Example 1 as a capacitive desalination electrode material;
[0034] Figure 8 It is a standard curve diagram between the NaCl concentration in the electrolyte solution and the conductivity of the electrolyte;
[0035] Fig. 9 This is the capacitive desalination cycle curve of the nanosheet composite hollow sphere prepared in Example 1 as a capacitive desalination electrode material;
[0036] Fig.10 This is a curve diagram of the number of cycles and the amount of salt adsorption corresponding to each cycle in a cycle experiment of the nanosheet composite hollow spheres prepared in Example 1 as a capacitor desalination electrode material. DETAILED DESCRIPTION
[0037] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] The present invention provides a nanosheet composite hollow sphere, wherein the particle size of the hollow sphere is 2-3 μm, and the thickness of the sphere wall of the hollow sphere is 300-500 nm;
[0040] The length of the nanosheet is 300-500 nm, and the thickness of the nanosheet is 5-10 nm;
[0041] The components of the nanosheets include basic nickel carbonate and nickel hydroxide.
[0042] In the present invention, the nanosheets are interconnected and attached to the shell surface of the hollow sphere, which greatly increases the contact surface between the material and the solution, and is more conducive to the specific adsorption of ions by the material in the subsequent capacitive desalination process, thereby improving the capacitive desalination performance of the material. Due to its unique structure, the nanosheet composite hollow sphere can provide more active sites as a capacitive desalination electrode material in the desalination process, increasing the contact area between the electrode material and the electrolyte, and the cavity structure inside the hollow sphere is also more convenient for the material to contact with the electrolyte, further improving the capacitive desalination performance of the material.
[0043] The present invention also provides a method for preparing nanosheet composite hollow spheres, the method comprising the following steps:
[0044] (1) mixing nickel nitrate hexahydrate, disodium ethylenediaminetetraacetate, water and an optional surfactant, and then performing a hydrothermal reaction;
[0045] (2) Adding an aqueous ammonia solution to the solution after the reaction in step (1), and then performing a hydrothermal reaction again.
[0046] In a specific embodiment, the weight ratio of nickel nitrate hexahydrate to disodium ethylenediaminetetraacetate is 1-2: 1. Specifically, the weight ratio of nickel nitrate hexahydrate to disodium ethylenediaminetetraacetate can be 1: 1, 1.5: 1 or 2: 1.
[0047] In a preferred embodiment, the weight ratio of nickel nitrate hexahydrate to disodium ethylenediaminetetraacetate is 2:1.
[0048] In a specific embodiment, the volume ratio of the ammonia solution to water is 2-4:35. Specifically, it can be 2:35, 3:35 or 4:35.
[0049] In a specific embodiment, the weight ratio of disodium ethylenediaminetetraacetate to water is 0.9-1.35:35, preferably 0.9:35. Specifically, it can be 0.9:35, 1:35, 1.1:35, 1.2:35 or 1.35:35.
[0050] In the method described in the present invention, it is necessary to strictly control the usage ratio of the nickel source and disodium ethylenediaminetetraacetate and the amount of ammonia solution added to strictly control the morphology of the obtained nanosheet composite hollow spheres. It is also necessary to control the amount of disodium ethylenediaminetetraacetate added to ensure that the obtained product has a complete hollow sphere morphology and to ensure the distribution of pore size types inside the obtained nanosheet composite hollow spheres, so that the pore size of the prepared material is more conducive to the penetration of ions in the electrolyte solution.
[0051] In a specific embodiment, the weight ratio of nickel nitrate hexahydrate to the surfactant is 1:0.3-1. Specifically, the weight ratio of nickel nitrate hexahydrate to the surfactant can be 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1.
[0052] In a preferred embodiment, the weight ratio of nickel nitrate hexahydrate to the surfactant is 1:0.5-0.7, and more preferably 1:0.66.
[0053] In the present invention, the surfactant is added to help the subsequently prepared nanosheet composite hollow spheres to be more evenly dispersed and less likely to agglomerate, so that they can be better used as electrode materials for capacitive desalination for water treatment. The surfactant can be polyvinyl pyrrolidone.
[0054] In the present invention, the aqueous ammonia solution is used to provide an alkaline environment required for the hydrothermal reaction, which is convenient for the generation of basic nickel carbonate and nickel hydroxide, and can also further control the morphology of the hollow spheres.
[0055] In a preferred embodiment, in step (2), when adding the aqueous ammonia solution, the aqueous ammonia solution can be added dropwise to the reacted solution obtained in step (1) under magnetic stirring.
[0056] In a specific embodiment, the concentration of the aqueous ammonia solution is 25-28 wt %.
[0057] In a specific embodiment, in step (1), the conditions of the hydrothermal reaction include: a reaction temperature of 150-200°C and a reaction time of 10-15h. Specifically, the temperature of the hydrothermal reaction may be 150°C, 160°C, 170°C, 180°C, 190°C or 200°C; and the reaction time may be 10h, 11h, 12h, 13h, 14h or 15h.
[0058] In a specific embodiment, in step (2), the conditions of the hydrothermal reaction include: a reaction temperature of 150-200°C and a reaction time of 10-15h. The temperature of the hydrothermal reaction can be 150°C, 160°C, 170°C, 180°C, 190°C or 200°C; and the reaction time can be 10h, 11h, 12h, 13h, 14h or 15h.
[0059] In the present invention, the hydrothermal reaction is carried out in a high-pressure reactor, the inner shell of the reactor is made of polytetrafluoroethylene and the outer shell is made of stainless steel.
[0060] In the present invention, the apparatus for heating may be an apparatus commonly used in the art for providing a reaction temperature for a reactor, for example, an oven or a muffle furnace.
[0061] In a specific embodiment, step (2) further comprises: centrifuging the solution after the reaction to obtain a precipitate, washing the precipitate alternately with ethanol and water for 3-5 times, and then drying it in a vacuum drying oven for 10-12 hours at a drying temperature of 50-70°C.
[0062] In a preferred embodiment, the rotation speed of the centrifugal separation is 8000-10000 rpm, and the time of the centrifugal separation is 5-10 min.
[0063] The third aspect of the present invention also provides a nanosheet composite hollow sphere prepared by the above method.
[0064] The fourth aspect of the present invention further provides an electrode material for capacitive desalination, wherein the electrode material for capacitive desalination comprises the above-mentioned nanosheet composite hollow sphere.
[0065] A fifth aspect of the present invention provides an application of the above-mentioned nanosheet composite hollow sphere in water treatment.
[0066] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0067] In the following examples and comparative examples, nickel nitrate hexahydrate, disodium ethylenediaminetetraacetate, and polyvinylpyrrolidone were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0068] Example 1
[0069] (1) 1.8 g of nickel nitrate hexahydrate, 0.9 g of disodium ethylenediaminetetraacetate and 1.2 g of polyvinyl pyrrolidone were weighed and dissolved in 35 mL of distilled water under magnetic stirring. The dissolved solution was then transferred to a 50 mL autoclave, which was sealed and placed in an electrically controlled oven for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 12 hours. After the reaction was completed, the autoclave was taken out and naturally cooled to room temperature.
[0070] (2) 4 mL of ammonia solution was added dropwise to the reaction solution obtained in step (1) under magnetic stirring. After mixing, the autoclave was placed in an electrically controlled oven for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 12 hours. After the reaction was completed, the autoclave was taken out and naturally cooled to room temperature. The reaction solution was then centrifuged at a speed of 8000 rpm for 6 min to obtain a lower precipitate. The precipitate was then washed alternately with distilled water and ethanol three times each, and finally dried in a vacuum oven at 60° C. for 12 h.
[0071] Example 2
[0072] (1) 1.8 g of nickel nitrate hexahydrate, 0.9 g of disodium ethylenediaminetetraacetate and 1.2 g of polyvinyl pyrrolidone were weighed and dissolved in 35 mL of distilled water under magnetic stirring. The dissolved solution was then transferred to a 50 mL autoclave, which was sealed and placed in an electrically controlled oven for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 12 hours. After the reaction was completed, the autoclave was taken out and naturally cooled to room temperature.
[0073] (2) Under magnetic stirring, 2 mL of ammonia solution was added dropwise to the reaction solution obtained in step (1), and after mixing, the autoclave was placed in an electrically controlled oven for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 12 hours. After the reaction was completed, the autoclave was taken out and naturally cooled to room temperature. The reaction solution was then centrifuged at a speed of 8000 rpm for 6 min to obtain a lower precipitate. The precipitate was then washed alternately with distilled water and ethanol three times each, and finally dried in a vacuum oven at 60° C. for 12 h.
[0074] Example 3
[0075] (1) Weigh 0.9 g of nickel nitrate hexahydrate, 0.9 g of disodium ethylenediaminetetraacetate, and 0.9 g of polyvinyl pyrrolidone, and dissolve all of them in 35 mL of distilled water under magnetic stirring. Then, transfer the dissolved solution to a 50 mL autoclave, seal the autoclave, and place it in an electrically controlled oven for hydrothermal reaction at a reaction temperature of 180° C. for 12 hours. After the reaction is completed, take out the autoclave and cool it naturally to room temperature.
[0076] (2) 4 mL of ammonia solution was added dropwise to the reaction solution obtained in step (1) under magnetic stirring. After mixing, the autoclave was placed in an electrically controlled oven for hydrothermal reaction at a reaction temperature of 180° C. for a reaction time of 12 hours. After the reaction was completed, the autoclave was taken out and naturally cooled to room temperature. The reaction solution was then centrifuged at a speed of 8000 rpm for 6 min to obtain a lower precipitate. The precipitate was then washed alternately with distilled water and ethanol three times each, and finally dried in a vacuum oven at 60° C. for 12 h.
[0077] Comparative Example 1
[0078] The method described in Example 1 was followed, except that in step (2), 6 mL of aqueous ammonia solution was added for reaction.
[0079] Comparative Example 2
[0080] The method described in Example 1 was followed, except that in step (1), 1.8 g of disodium ethylenediaminetetraacetate was added.
[0081] Test Case
[0082] Test Example 1
[0083] The nanosheet composite hollow spheres prepared in Example 1 were tested by X-ray powder diffraction. The results are as follows: Figure 1 shown.
[0084] Depend on Figure 1 It can be seen that the nanosheet composite hollow sphere material of the present invention has weak crystallinity, and the material contains more amorphous substances, and the amorphous substances are more active than the crystalline substances, and the activation energy is lower. Therefore, when the nanosheet composite hollow sphere of the present invention is used as an electrode material for capacitive desalination, its ion adsorption performance is more superior. In addition, the diffraction peak of the nanosheet composite hollow sphere material of the present invention coincides with the peak position of the basic nickel carbonate with PDF card number 38-0714 and the nickel hydroxide with PDF card number 14-0117, indicating that the basic nickel carbonate / nickel hydroxide nanosheet composite hollow sphere material is successfully synthesized by the method described in the present invention.
[0085] Test Example 2
[0086] The nanosheet composite hollow spheres prepared in Example 1 were characterized by infrared spectrometer. Figure 2 shown.
[0087] Depend on Figure 2 It can be seen that the infrared spectrum is at 3452cm -1 The characteristic peak of -OH is at 2928cm -1 and 1599cm -1 Corresponding to the stretching and bending vibration peaks of crystal water, the characteristic peaks of ν(CO3) / CO, ν(C=O), δ(CO3), and ρ(OCO) are at 1385, 1066, 833, and 667 cm -1 Appear, all of which are CO3 2- The characteristic peaks of 955cm -1 、534cm -1 、428cm -1 The characteristic peak of Ni-OH indicates that Ni-OH and CO3 do exist in the nanosheet composite hollow spheres of the present invention. 2- and -OH, which indirectly verifies that the synthesized nanosheet composite hollow spheres contain basic nickel carbonate and nickel hydroxide.
[0088] Test Example 3
[0089] The nanosheet composite hollow spheres prepared in Example 1 were characterized by using a BET specific surface area tester. The nitrogen adsorption-desorption curve and pore size distribution of the material are shown in FIG. Figure 3 As shown, Figure 3 A is the nitrogen adsorption-desorption curve of the material, Figure 3 B is the pore size distribution diagram of the material.
[0090] Nitrogen adsorption / desorption curve of the nanosheet composite hollow sphere prepared according to Example 1 Figure 3 A shows that the hysteresis loop in the figure shows that the hysteresis loop is an H4 type mesoporous structure, and the specific surface area of the material is as high as 298.6m 2 / g -1 , the large specific surface area can provide more active sites for ion adsorption in subsequent electrochemical reactions.
[0091] The pore size distribution of the nanosheet composite hollow spheres prepared according to Example 1 Figure 3 B shows that the pore size inside the material is concentrated in the micropore area of 1.8nm and the mesopore area of 3-12nm. The pore size distribution inside the material is more conducive to the penetration of electrolyte ions and can facilitate full contact between the material and the electrolyte.
[0092] Test Example 4
[0093] The morphology of the nanosheet composite hollow spheres prepared in Examples 1-3 and Comparative Examples 1-2 was tested by SEM. The test results are as follows: Figure 4 a-4f. Among them, Figure 4 4a and 4b are morphological images of the nanosheet composite hollow spheres prepared in Example 1. Figure 4 c is the morphology of the nanosheet composite hollow sphere prepared in Example 2, Figure 4 d is the morphology of the nanosheet composite hollow sphere prepared in Example 3, Figure 4 e is the morphology of the product prepared in Comparative Example 1, Figure 4 f is the morphology of the product prepared in Comparative Example 2. From the SEM image of the nanosheet composite hollow sphere, it can be seen that the particle size of the nanosheet composite hollow sphere prepared by the present invention is 2-3 μm, the hollow sphere particle size is uniform, the morphology is complete and evenly dispersed, the spherical shell is interconnected nanosheets, and the length and width of the nanosheets are 400-500nm. However, from the morphology of the product prepared in Comparative Examples 1-2, it can be seen that when the amount of ammonia solution and disodium ethylenediaminetetraacetate exceeds the range specified by the present invention, the morphology of the obtained product changes significantly, and it is not a hollow sphere, and the stacking is serious, which affects the contact between the subsequent product and the electrolyte.
[0094] The morphology of the nanosheet composite hollow spheres prepared in Example 1 was tested by TEM. The test results are as follows: Figure 4From the TEM image of the material, it can be seen that the product prepared by the present invention is determined to be a hollow sphere morphology, and its test results are consistent with the SEM of the material. The thickness of the nanosheet is 5-10nm, and the thickness of the hollow sphere wall is 300-500nm.
[0095] Test Example 5
[0096] The electrochemical properties of the nanosheet composite hollow spheres prepared in Example 1 were characterized and tested using cyclic voltammetry (CV) and constant current charge-discharge (GCD) methods.
[0097] Specific test method: The test was carried out using an electrochemical workstation (Chenhua CHI-660E). The nanosheet composite hollow spheres prepared in Example 1 were mixed with the binder polyvinylidene fluoride and Ketjen black in a weight ratio of 8:1:1, and then coated on a 1×1 cm 2 The graphite plate was dried as the working electrode, Ag / AgCl was the reference electrode, platinum wire was the counter electrode, and the electrolyte solution was a solution with a NaCl concentration of 500 ppm.
[0098] The current range of the CV test is -0.6V-0.6V, and the scanning speed is 2mv / s, 5mv / s, 10mv / s, 20mv / s and 50mv / s. The test results are as follows: Figure 5 As shown in the figure, the nanosheet composite hollow spheres prepared by the method described in the present invention as a capacitor desalination electrode material have a pair of obvious redox peaks, which correspond to Na + This shows that the nanosheet composite hollow spheres of the present invention have certain capacitive desalination potential and can be well applied to capacitive desalination electrode materials.
[0099] The voltage of GCD test is -0.6V-0.6V, and the test results are as follows Figure 6 As shown in the figure, it can be seen through calculation that the specific capacitance values of the electrode material of the nanosheet composite hollow sphere of the present invention are 40.7F / g, 31.7F / g, 22.5F / g and 21.7F / g respectively when the current density is 2A / g, 5A / g, 10A / g and 20A / g, showing good rate performance at high current density, indicating that the nanosheet composite hollow sphere of the present invention has a higher electrode energy storage capacity and can be used to adsorb more ions in the process of capacitive desalination.
[0100] Test Example 6
[0101] The capacitive desalination performance of the nanosheet composite hollow spheres prepared in Example 1 was characterized and tested.
[0102] Specific test method: The test was carried out using a two-electrode device, which consisted of a working electrode, an ion exchange membrane, and a diaphragm. The asymmetric membrane capacitive deionization device was controlled by a Zhaoxin DC power supply (MN-155D). The nanosheet composite hollow sphere binder polyvinylidene fluoride and Ketjen black prepared in Example 1 were mixed in a weight ratio of 8:1:1, and the mixture was evenly coated on a 4×4 cm 2 After drying on the titanium mesh, it was used as a working electrode to test its capacitive desalination performance, and the conductivity of the electrolyte was measured by a conductivity meter (Shanghai Leici, DDSJ308F).
[0103] During the test of capacitor desalination, the conductivity change diagram of the electrolyte under the state of ion adsorption-desorption of the electrode material is shown in the figure. The operating voltage is set to 1.2V. The test results are as follows: Figure 7 As shown in the figure, when the electrode material is powered at 1.2V, the ions in the electrolyte are adsorbed by the electrode, resulting in a significant decrease in the conductivity of the electrolyte. When a reverse voltage is applied, the ions in the electrolyte are desorbed from the electrode, and the conductivity of the electrolyte rises again, indicating that the nanosheet composite hollow spheres described in the present invention have good reversible electrical adsorption properties as a capacitor desalination electrode material, and can be very well applied in the field of capacitor desalination water treatment.
[0104] The standard curve between the NaCl concentration in the test electrolyte solution and the electrolyte conductivity is as follows: Figure 8 As shown in the figure, the NaCl concentration in the electrolyte solution is proportional to the conductivity of the solution, and the linear relationship is good, indicating that there is a positive correlation between the two. The NaCl concentration in the electrolyte at this time can be obtained by testing the conductivity of the electrolyte, thereby calculating the desalination capacity of the capacitive desalination electrode material.
[0105] Test the capacitance desalination cycle curve of the electrode material: set the operating voltage to 1.2V, test the change of electrolyte conductivity over time, and after reaching adsorption saturation, short-circuit the positive and negative plates, and then test the change of electrolyte conductivity over time during the desorption of ions from the electrode material. Cycle this adsorption-desorption process 20 times to obtain the capacitance desalination cycle curve of the electrode material. The test results are as follows: Fig. 9 shown.
[0106] Depend on Fig. 9 It can be seen that during the 20 cycles of adsorption-desorption of the nanosheet composite hollow spheres described in the present invention, the curve trend and shape of the conductivity of the electrolyte changing with time are basically consistent, indicating that the nanosheet composite hollow spheres described in the present invention exhibit good electrical adsorption performance, can quickly respond to the transition of electrical adsorption-desorption, and have excellent cycle performance.
[0107] The curve of the salt adsorption amount of the electrode material corresponding to each cycle in the 20 cycle test is shown in the following figure. Fig.10 shown.
[0108] The calculation formula of salt adsorption is: e =V(C0-C1) / w, where q e The amount of salt adsorbed per unit active material, V refers to the volume of the electrolyte, C0 is the initial concentration of NaCl in the electrolyte before each cycle, C1 is the lowest concentration of NaCl that can be achieved after electrolyte adsorption in each cycle, and w is the mass of the positive and negative electrode sheets;
[0109] Among them, V is 40mL, W is 16.88mg, C0 and C1 are based on Figure 8 The calculation is performed based on the standard curve diagram between the NaCl concentration in the electrolyte solution and the electrolyte conductivity shown in FIG. 1 , thereby obtaining the salt adsorption amount corresponding to each cycle of the capacitive desalination electrode material obtained in Example 1.
[0110] Depend on Fig.10 It can be seen that the nanosheet composite hollow spheres of the present invention are used as electrode materials for capacitive desalination. In 20 capacitive desalination cycle experiments, the salt adsorption amount corresponding to each cycle is 31.6 mg / g, 34.0 mg / g, 32.8 mg / g, 31.6 mg / g, 38.8 mg / g, 41.3 mg / g, 40.1 mg / g, 40.1 mg / g, 35.2 mg / g, 40.1 mg / g, 37.6 mg / g, 31.6 mg / g, respectively. / g, 37.6mg / g, 36.4mg / g, 36.4mg / g, 31.6mg / g, 36.4mg / g, 37.6mg / g, 32.8mg / g and 31.6mg / g. It can be seen that the nanosheet composite hollow spheres described in the present invention exhibit strong cycle stability, and the performance is maintained at 100% in 20 cycles for up to 3 days. In addition, the salt adsorption capacity is large and the adsorption performance is excellent. It can be used as an electrode material for capacitive desalination for water treatment.
[0111] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An electrode material for capacitive desalination, characterized in that: The electrode material includes nanosheet composite hollow spheres; The preparation method of the nanosheet composite hollow sphere comprises the following steps: (1) nickel nitrate hexahydrate, disodium ethylenediaminetetraacetate, water and a surfactant are mixed, and then subjected to a hydrothermal reaction; (2) adding an aqueous ammonia solution to the solution after the reaction in step (1), and then performing a hydrothermal reaction again; The weight ratio of nickel nitrate hexahydrate to disodium ethylenediaminetetraacetate is 1-2:1; The volume ratio of ammonia solution to water is 2-4:35; The weight ratio of disodium edetate to water is 0.9-1.35:35; The particle size of the hollow sphere is 2-3 μm, and the wall thickness of the hollow sphere is 300-500 nm; The length of the nanosheet is 300-500 nm, and the thickness of the nanosheet is 5-10 nm; The components of the nanosheets include basic nickel carbonate and nickel hydroxide.
2. The electrode material according to claim 1, characterized in that The weight ratio of nickel nitrate hexahydrate to the surfactant is 1:0.3-1.
3. The electrode material according to claim 1, characterized in that The concentration of the ammonia solution is 25-28wt%.
4. The electrode material according to claim 1, characterized in that In step (1), the conditions of the hydrothermal reaction include: reaction temperature of 150-200° C., and reaction time of 10-15 h.
5. The electrode material according to claim 1, characterized in that In step (2), the conditions of the hydrothermal reaction include: reaction temperature of 150-200° C., and reaction time of 10-15 h.
6. Use of the electrode material for capacitive desalination according to any one of claims 1 to 5 in water treatment.
Citation Information
Patent Citations
Nickel hydroxide nanosheet thin-film material as well as preparation method and application thereof
CN102891008A